Can the Rwandan Catholic Church Overcome its History of Politicization? A Reply to Philippe Denis - Anthony Court (Journal for the Study of Religion)
Scholarly interest in Rwanda ranges across all aspects of its history. A substantial body of influential research appeared particularly during the two decades following independence in 1962. These contributions together with earlier work constitute the bedrock of later research, including the intensive focus on the mass violence in Rwanda during the first half of the 1990s and its consequences for the Great Lakes region. One of the most controversial questions to emerge from the occurrences of the 1990s has been the role of the churches, and particularly the dominant Roman Catholic Church, in the violence manifesting in its most extreme form in the genocide of 1994. This article addresses the claim by the scholar Philippe Denis in his essay ‘Christian gacacaand official gacacain post-genocide Rwanda’ (Denis 2019:1-27of 27) that the Rwandan Catholic Church has played a leading role in the difficult process of post-genocide reconciliation. Denis provides us with an authoritative account of the emergence and functioning of the Christian gacacaand its relation to the official, state-sponsored gacaca. Moreover, he presents grounds for his claim that this pastoral initiative helped to alleviate the tension that arose between the church and the Rwandan Patriotic Front(RPF)-dominated state in the aftermath of the genocide when the institutional church was widely condemned for its silence during the genocide and even for its complicity in the genocide. The question that I wish to pose is whether,by not broadening thefocus placed by the church on the problem of ethnic animosity or ‘ethnocentrism’ as the principal causal factor that ‘led’ to the genocide, Denis does not elide a range of trigger factors that shouldbe taken into account in any assessment of both the genocide and the church’s role in it. I aim to show that,by not taking into account these important factors and their relevance for interpreting the historically close ties between church and state, Denis tends to endorse the church’s reductionist interpretation of the history of intergroup conflict and mass violence, which it attributes almost exclusively to ethnic animosity. Consequently, when in the aftermath of the genocide,the church declared that ‘ethnism’ lay at the heart of all social and politicalills, moreover refusing to acknowledge its own role in propagating a state ideology of ethnic racism, it not only risked re-inscribing a binary-logic that guided its thinking and defined its role in the Rwandan politics throughout the 20thcentury, but alsodeflected attention away from its problematic assumption of moral authority to mediate between perpetrators and victims/survivors.